Regional impairment of deep gray matter perfusion in neonates with congenital heart disease revealed by arterial spin labeling MRI - Sun, Yan; Liu, Yujie; Yu, Wenwen; Zhong, Yumin (Frontiers in Human Neuroscience, 2022)
The present study examined deep gray matter perfusion in neonates with congenital heart disease (CHD) with arterial spin labeling magnetic resonance imaging preoperatively. We found that neonates with cyanotic CHD showed lower right thalamus compared with controls and lower right basal ganglia perfusion compared with acyanotic CHD. When CHD group was assessed as a whole, it showed slightly decreased left thalamus perfusion compared with controls. The results suggest that cardiac physiology plays a crucial part in changes in regional cerebral perfusion. Perfusion with arterial spin labeling may be a useful marker of high risk for impaired cerebral blood flow auto-regulation and cerebral hypoperfusion in neonates with CHD.